Distribution competence of a football clubs goalkeepers - Seaton, M.; Campos, J. (International Journal of Performance Analysis in Sport, 2011)
Much of the existing goalkeeper (GK) research is based around GK's performance but not with a match analysis theme. Research has focused on physiology, psychology and injury prevention. Performance analysis based GK research will significantly increase the standards of GK performance by increasing the knowledge we have of a GK's match demands. As a consequence of this lack of knowledge surrounding GK's distribution performance the aim of this study was to increase the understanding of GK's performance through their distribution performance and to see if the level in which they compete influences this. The subjects used in this study were all professional GK's from the same club, they were all the first choice GK's from the clubs 4 most senior teams. The study analysed the GK's distribution performances through Distribution Location, Type, Success and Outcome data. Results found that there were significant differences (P<0.05) in the GK's Location, Type and Success of distributions. This research has found that the GK's did indeed perform differently and that GK's do truly perform to better standards as their level of competition increases, this is shown by performing simpler tasks to a near perfect standard and performing more difficult tasks well.